Eksplorasi hubungan layanan dan kontribusi Pendidikan Agama Islam pada kepribadian siswa SMPN 1 Bojong Gede - Muhardi (Program Studi Magister Pendidikan Agama Islam, 2024)
This study aims to identify the relationship between Educational Services and the Role of Islamic Religious Education with Student Personality at SMP Negeri 1 Bojong Gede. The survey method was used with 225 students as respondents. Data was collected through questionnaires to measure students' perceptions of Educational Services and the Role of Islamic Religious Education. Assessment of Student Personality using instruments that have been registered and calibrated for validity and reliability. The results of the analyses showed that: (1) There is a positive relationship between Educational Services (X1) and Student Personality (Y) with coefficient ry1 = 0.360 and regression equation y = 5.077 + 0.144 X1; (2) Positive relationship between Role of Islamic Education (X2) and Student Personality (Y) with coefficient ry2 = 0.299 and regression equation y = 6.660 + 0.079 X2; (3) A joint positive relationship between Educational Services (X1) and the Role of Islamic Religious Education (X2) with Student Personality (Y), with coefficient ry12 = 0.377 and multiple regression equation y = 3.493 + 0.113 X1 + 0.037 X2. These findings indicate the need for increased educational services at home and increased role of Islamic Education to improve student achievement and personality. The implementation of the Role of Islamic Education can be improved through mobilising direction, providing motivation, and more effective supervision of staff and teachers. Abstrak Penelitian ini bertujuan untuk mengidentifikasi hubungan antara Layanan Pendidikan dan Peran Pendidikan Agama Islam dengan Kepribadian Siswa di SMP Negeri 1 Bojong Gede. Metode survei digunakan dengan 225 siswa sebagai responden. Pengumpulan data dilakukan melalui kuesioner untuk mengukur persepsi siswa terhadap Layanan Pendidikan dan Peran Pendidikan Agama Islam. Penilaian Kepribadian Siswa menggunakan instrumen yang telah terdaftar dan dikalibrasi untuk validitas dan reliabilitas. Hasil analisis menunjukkan bahwa: (1) Terdapat hubungan positif antara Layanan Pendidikan (X1) dengan Kepribadian Siswa (Y) dengan koefisien ry1 = 0,360 dan persamaan regresi y = 5,077 + 0,144 X1; (2) Hubungan positif antara Peran Pendidikan Agama Islam (X2) dan Kepribadian Siswa (Y) dengan koefisien ry2 = 0,299 dan persamaan regresi y = 6,660 + 0,079 X2; (3) Hubungan positif bersama antara Layanan Pendidikan (X1) dan Peran Pendidikan Agama Islam (X2) dengan Kepribadian Siswa (Y), dengan koefisien ry12 = 0,377 dan persamaan regresi ganda y = 3,493 + 0,113 X1 + 0,037 X2. Temuan ini menunjukkan perlunya peningkatan Layanan Pendidikan di rumah dan peningkatan Peran Pendidikan Agama Islam untuk meningkatkan prestasi dan Kepribadian Siswa. Implementasi Peran Pendidikan Islam dapat ditingkatkan melalui mobilisasi arah, pemberian motivasi, dan pengawasan yang lebih efektif terhadap staf dan guru.